Development of a wide-width raster scanning optical system for high-resolution ultraviolet laser direct micro-patterning. (November 2020) - Park, JongBok; Choi, Hyun; Lim, Geon; Lee, Dong-Kil; Park, No-Cheol; Kim, Wan-Chin
Highlights: Compact raster scanning optics for high-resolution micro-patterning on wide-width format was developed. The design performance was verified using optical characteristic measurements. The photoresist pattern generated uniform patterns without distinctive defects. The novel optical system could be broadly applied in commercial laser scanning systems. Abstract: We developed F-theta raster scanning optics for high-resolution ultraviolet (UV) beam direct micro-patterning, capable of machining on a 300-mm wide image with a confined beam spot of less than 20 μm, a 13.5% spot size. To achieve the imaging performance with resolution, F-theta optics based on synthetic silica glass were designed using a high-power laser light source with a wavelength of 355 nm. In addition, to improve the difficulty of optical alignment in conventional systems and the scan linearity between the scan angle and exposing position, F-theta scanning optics were designed to contain two lenses with a rotationally asymmetric high-order polynomial surface. The designed optical system showed a performance of 20 ± 2 μm at the full width of a 1/ e 2 maximum intensity value through a 0.8 mm focal depth. The scanning linearity error and root-mean-square (RMS) wavefront error were designed to be less than 0.2% and 0.05 λ, respectively. The design performance was verified using optical characteristic measurements and actual patterning experiments with the optics composed of proto lenses